2008
DOI: 10.1128/jb.01477-07
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of YfgL and YaeT Interactions through Bioinformatics, Mutagenesis, and Biochemistry

Abstract: In Escherichia coli, YaeT, together with four lipoproteins, YfgL, YfiO, NlpB, and SmpA, forms a complex that is essential for ␤-barrel outer membrane protein biogenesis. Data suggest that YfgL and YfiO make direct but independent physical contacts with YaeT. Whereas the YaeT-YfiO interaction needs NlpB and SmpA for complex stabilization, the YaeT-YfgL interaction does not. Using bioinformatics, genetics, and biochemical approaches, we have identified three residues, L173, L175, and R176, in the mature YfgL pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(159 citation statements)
references
References 44 publications
4
153
0
2
Order By: Relevance
“…Considering its relatively low abundance in the eluates and the fact that BamB did not appear to be required for Hbp secretion, its copurification with the Hbp110C/348C intermediate may reflect secondary cross-linking to BamA rather than a direct interaction with the intermediate itself. In any case, a close proximity of BamB is likely, since a direct interaction between BamA and BamB has been demonstrated recently (Vuong et al, 2008). The copurification of OmpA is more enigmatic since it is not a known constituent of the Bam complex.…”
Section: Discussionmentioning
confidence: 99%
“…Considering its relatively low abundance in the eluates and the fact that BamB did not appear to be required for Hbp secretion, its copurification with the Hbp110C/348C intermediate may reflect secondary cross-linking to BamA rather than a direct interaction with the intermediate itself. In any case, a close proximity of BamB is likely, since a direct interaction between BamA and BamB has been demonstrated recently (Vuong et al, 2008). The copurification of OmpA is more enigmatic since it is not a known constituent of the Bam complex.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, BamC, BamD and BamE interact with BamA as a group, while the BamA-BamB interaction is independent of the other lipoproteins (Malinverni et al, 2006;Sklar et al, 2007;Vuong et al, 2008). In mutants lacking either BamC or BamE, BamD levels are normal but less BamD is associated with BamA.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of the E. coli BAM complex identified alleles of bamB (yfgL) that caused little or no phenotypic defect, yet weakened the interaction between BamB and BamA in co-immunoprecipitation experiments, suggesting that the affected amino acids are important for BAM complex stability (Vuong et al, 2008). To generate intermediate defects in chemical sensitivity (Table 2), either the function of Caulobacter BamEDC or the stability of the resulting BAM complex could be compromised.…”
Section: Under Conditions Of Phosphate Limitation Wild-typementioning
confidence: 99%
See 1 more Smart Citation
“…Many in vitro and in vivo studies have investigated various components involved in this pathway (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). However, in vitro experiments typically characterize individual components in isolation, and in vivo studies are often incapable of deciphering how specific components are responsible for observed phenomena.…”
mentioning
confidence: 99%